Antibiotic prophylaxis or granulocyte-colony stimulating factor support in multiple myeloma patients undergoing autologous stem cell transplantation - Klein, Eva-Maria; Sauer, Sandra; Klein, Sabrina; Tichy, Diana; Benner, Axel; Bertsch, Uta; Brandt, Juliane; Kimmich, Christoph; Goldschmidt, Hartmut; Müller-Tidow, Carsten; Jordan, Karin; Giesen, Nicola (Cancers, 2021)
We compare, in this manuscript, antibiotic prophylaxis versus granulocyte-colony stimulating factor (G-CSF) support as anti-infective strategies, in patients with multiple myeloma (MM), undergoing high-dose therapy followed by autologous stem cell transplantation (HDT/ASCT). At our institution, antibiotic prophylaxis after HDT/ASCT in MM was stopped in January 2017 and replaced by G-CSF support in March 2017. Consecutive MM patients who received HDT/ASCT between March 2016 and July 2018 were included in this single-center retrospective analysis. In total, 298 patients and 353 individual cases of HDT/ASCT were evaluated. In multivariate analyses, G-CSF support was associated with a significantly shortened duration of severe leukopenia < 1/nL (p < 0.001, hazard ratio (HR) = 16.22), and hospitalization (estimate = −0.19, p < 0.001) compared to antibiotic prophylaxis. Rates of febrile neutropenia, need of antimicrobial therapy, transfer to intensive care unit, and death, were similar between the two groups. Furthermore, antibiotic prophylaxis was associated with a significantly increased risk for the development of multidrug resistant bacteria especially vancomycin-resistant Enterococcus faecium compared to G-CSF support (odds ratio (OR) = 17.38, p = 0.01). Stop of antibiotic prophylaxis as an anti-infective strategy was associated with a reduction in overall resistance rates of bacterial isolates. These results indicate that G-CSF support should be the preferred option in MM patients undergoing HDT/ASCT.